A hierarchical model of the determinants of non-performing assets in banks: an ISM and MICMAC approach. Issue 35 (27th July 2019) - Rizvi, Noor Ulain; Kashiramka, Smita; Singh, Shveta; Sushil,
ABSTRACT: The banking systems of emerging economies in general and India in particular are facing sustained impairment due to mounting non-performing assets (NPAs). In the absence of stringent policies and their implementation, the results will be detrimental and may eventually lead to an economic crisis. Thus, it is imperative to unearth the causal factors and mitigate the risks involved with rising NPAs. The study attempts to identify the determinants of NPAs from the existing literature and subsequently, explore the interlinkages between the identified factors. A model of these factors is developed using Interpretive Structural Modeling (ISM) and MICMAC approach. Key managerial insights were obtained by the suggested model, specific to the Indian context. The hierarchical model provides a clearer perspective about the relationship between the factors and suggests that economic conditions and political factors are the key drivers which impact the ownership pattern and adherence to the regulatory framework; these further impact the internal factors related to the banks and borrowers' capacity to repay. The study will act as a scaffolding for policymakers and bankers. Based on these findings, better instruments and mechanisms for recovery/management of NPAs can be put in place.